The First Principle Approach in Estimating Bulk Modulus Based on Explicit Expression of Canonical Partition Function - Mangelli, H.; Vafaeei, M.; Mansoori Oghaz, N.; Haghighi, B. (Physics and Chemistry of Solid State, 2020)
The bulk modulus is one of the most important characteristic features of solids. Accordingly, we have developed a statistical-mechanical treatment based on an equation which enables us to calculate the bulk modulus for solids with the minimum manifold of input data. In our model, a conjunction between Gruneisen parameter and canonical partition function has been established. We have found out that the volume dependency of Gruneisen parameter is critical in estimating bulk modulus. The result for hexagonal closed- packed (hcp) iron is very good and commensurate with the best measurements. This framework can be extended to the other elemental solids or a variety of compounds.